2021
DOI: 10.1111/grs.12333
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics of Erianthus arundinaceus as a bedding material for broiler

Abstract: This study was conducted to evaluate the physical characteristics of the biomass crop Erianthus arundinaceus as a bedding material for broiler and to compare it with existing bedding materials. Three physical characteristics were evaluated: the water absorbability, the water-holding capacity, and the cushioning property. E. arundinaceus, shredded to five different particle sizes, was compared with sawdust, which is a typical bedding material used worldwide, and three alternatives: recycled paper, rice husks, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…High moisture in the bedding increases ammonia build-up through increased microbial metabolism, resulting in respiratory lesions [18], whereas a low moisture content assures a longer storage period of the bedding material since it affects the litter's physical and handling properties such as compressibility, compaction, and cohesion [23]. Hemp shives (7.78%) showed similar moisture content to other bedding materials such as wood shavings (7.1 and 7.37%), corn stover (8.06%), rice hulls (8.37, 8.7, 10%), and wheat straw (8.44%) [23][24][25][26], but higher moisture content than recycled paper (3.82%), rice husks (4.62%), and sawdust (4.83%) [22].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…High moisture in the bedding increases ammonia build-up through increased microbial metabolism, resulting in respiratory lesions [18], whereas a low moisture content assures a longer storage period of the bedding material since it affects the litter's physical and handling properties such as compressibility, compaction, and cohesion [23]. Hemp shives (7.78%) showed similar moisture content to other bedding materials such as wood shavings (7.1 and 7.37%), corn stover (8.06%), rice hulls (8.37, 8.7, 10%), and wheat straw (8.44%) [23][24][25][26], but higher moisture content than recycled paper (3.82%), rice husks (4.62%), and sawdust (4.83%) [22].…”
Section: Discussionmentioning
confidence: 67%
“…Unfortunately, we do not have any information about the nature of either of these samples to offer any further discussion. In previous studies, water absorption of bedding materials was reported and showed values of 266% for fine wood shavings, 305% for cereal straw, 320.8% for wheat straw, 330% for straw, 382% for recycled paper, 392.3% for paper cuttings, 315.9% and 460% for wood shavings, 462% for rice husks and 483% for sawdust [1,19,22,28]. This suggests that hemp shives may have a similar water absorption capacity to fine wood shavings which are known for their good moisture absorption.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Appropriate bedding characteristics improve chicken production performance. In addition, the particle size of the bedding material was found to play an essential role in the development of FPD [ 46 , 47 ]. Thus, our research suggested that the lower incidence of FPD in chickens kept on CHs, especially pellets, was also due to their size compared to wheat-chopped straw.…”
Section: Discussionmentioning
confidence: 99%